MEASUREMENT OF VOID FRACTION USING ELECTRICAL CAPACITANCE TOMOGRAPHY FOR AIR-WATER CO-CURRENT BUBBLE COLUMN - SHAFQUET, AREEBA SHAFQUET (2011)
In process industries, the measurement of void fraction is considerably important for sustainable operations. It largely affects the mass flow rate of gas and liquid in a two-phase flow. The erroneous calculation of void fraction is inevitably be the cause of many industrial accidents such as loss of coolant accidents in nuclear reactor, sweet corrosions in sub-sea oil and gas pipelines and an in-efficient process control of chemical plants. The customary approach for two-phase flow measurement separates the two-phases first and then measures the mixture as individual components. These methods are not favorable as they may result in the disruption of incessant industrial processes. Due to these limitations, a non-invasive, experimental study was conducted by using Electrical Capacitance Tomography (ECT) technique and differential pressure (ΔP) technique on a co-current vertical gas-liquid flow in a bubble column. A series of experiments were performed by regulating the flow rates of air and deionized water in the co-current bubble column to investigate flow regime, void fraction and pressure drop etc. The flow characteristics were physically investigated by using visual instruments. A bubble flow regime map was developed for air superficial velocity range of 0.00218 – 0.03 m/sec and water superficial velocity range of 0.00425 – 0.034 m/sec. It also classified the gas-liquid flow in a bubble column as discrete, dispersed and coalesced bubble flow regime under the stipulated experimental conditions. The raw data obtained from ECT images used for calculating void fraction were analysed by using distribution models and simulations using COMSOL. The comparison of simulation results with experimental data shows an average percentage deviation of + 20%. The estimation of void fraction in a bubble column via differential pressure method shows the influence of superficial gas velocity on void fraction as a linear function which agrees with the void fraction obtained from ECT measurements. Finally, the experimental data of bubble sizes and void fraction was also compared with the precedent correlations which generally show a good conformity with the results.